TRAJEKTORI KEBIJAKAN DAN KONFLIK SOSIO-EKOLOGIS DALAM WACANA POLITIK FOOD ESTATE DI MERAUKE - Hutabarat, Dayinta; Pangaribuan, Christian Samuel (Triwikrama: Jurnal Ilmu Sosial, 2025)
This study examines the policy trajectory of the food estate program in Merauke and the socio-ecological conflicts that emerge within the political development discourse of the Joko Widodo administration. The food estate, promoted as a solution to national food security, has instead generated various issues ranging from agronomic unsuitability and large-scale land clearing without adequate environmental assessments to conflicts over the living spaces of Indigenous communities. Using a qualitative approach with the Policy Ethnography method, this research traces the processes of policy formulation, implementation, and field-level practices, as well as how government political narratives frame the project as a national strategic agenda. The findings show that the food estate in Merauke not only failed to meet its production targets but also caused damage to peat ecosystems, increased carbon emission risks, and threatened the socio-cultural sustainability of Indigenous communities. Furthermore, discourse analysis reveals that the government employed food security and agricultural modernization framing to obscure the program’s ineffectiveness and reinforce political legitimacy. These findings indicate that the failure of the food estate is structural, influenced by power relations, development patterns, and minimal ecological consideration. This research underscores the importance of socially and environmentally grounded policy evaluation and the protection of Indigenous rights in formulating sustainable food policies in Indonesia. Keyword: Food Estate, Socio-Ecological Conflict, Political Discourse, Policy Trajectory, Indigenous Communities Abstrak Penelitian ini mengkaji trajektori kebijakan food estate di Merauke serta konflik sosio-ekologis yang muncul dalam konteks wacana politik pembangunan era Joko Widodo. Food estate yang dipromosikan sebagai solusi ketahanan pangan nasional ternyata menimbulkan berbagai persoalan mulai dari ketidaksesuaian agronomis, pembukaan lahan skala besar tanpa kajian lingkungan memadai, hingga konflik ruang hidup masyarakat adat. Melalui pendekatan kualitatif dengan metode Etnografi Kebijakan, penelitian ini menelusuri proses perumusan, implementasi, dan praktik kebijakan di lapangan, serta bagaimana narasi politik pemerintah membingkai proyek ini sebagai agenda strategis nasional. Hasil penelitian menunjukkan bahwa food estate di Merauke tidak hanya gagal memenuhi target produksi, tetapi juga menimbulkan kerusakan ekosistem gambut, meningkatkan risiko emisi karbon, serta mengancam keberlanjutan sosial-budaya masyarakat adat. Selain itu, analisis wacana memperlihatkan bahwa pemerintah menggunakan framing ketahanan pangan dan modernisasi pertanian untuk menutupi ketidakefektifan program dan melanggengkan legitimasi politik. Temuan ini memperlihatkan bahwa kegagalan food estate bersifat struktural, dipengaruhi oleh relasi kuasa, pola pembangunan dengan menggunakan kebijakan publik, serta minimnya pertimbangan ekologis. Penelitian ini menegaskan pentingnya evaluasi kebijakan berbasis sosial-lingkungan dan perlindungan hak masyarakat adat dalam merumuskan kebijakan pangan yang berkelanjutan di Indonesia. Kata Kunci: Food Estate, Merauke, Konflik Sosio-Ekologis, Wacana Politik, Masyarakat Adat